2018
DOI: 10.1155/2018/3742362
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Delayed Sternal Closure in Pediatric Heart Surgery: Single-Center Experience

Abstract: Background Delayed sternal closure (DSC) after cardiac surgery is a therapeutic option in the treatment of the severely impaired heart in pediatric cardiac surgery. Methods A single-center retrospective review of all bypass surgeries performed over a 10-year period (2003–2012). Results Of a total of 2325 patients registered in our database, the DSC group included 259 cases (11%), and the remaining 2066 cases (89%) constituted the control group (PSC). RACHS-1 risk was higher for the DSC group (74% had a score o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…Samir et al 14 in their study of 312 neonates found that preoperative inotropic support was not related with mortality as was seen in this study. Sierra et al 34 found that risk adjustment for congenital heart surgery (RACHS-1) score > 3 predicts mortality which corroborated well with our study (p < 0.001). Longer ACC time translates into a complex cardiac surgery, which has been found to be associated with mortality.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Samir et al 14 in their study of 312 neonates found that preoperative inotropic support was not related with mortality as was seen in this study. Sierra et al 34 found that risk adjustment for congenital heart surgery (RACHS-1) score > 3 predicts mortality which corroborated well with our study (p < 0.001). Longer ACC time translates into a complex cardiac surgery, which has been found to be associated with mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Longer ACC time translates into a complex cardiac surgery, which has been found to be associated with mortality. 17,20,34,35 Similar finding was observed in our study (p < 0.001), however, duration of CPB was not found to be related to mortality (p = 0.94). In addition, the postoperative factors such as requirement of re-explorations (p < 0.001), duration of DSC (p < 0.001), duration of postoperative MV (p < 0.001), and development of culture-proven sepsis (p = 0.002) and mediastinitis (p = 0.03) contributed significantly to mortality, as has been corroborated by other studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the outward, it may seem that leaving the sternum open, compared to primary sternal closure, suggests a high risk for mortality [12,13] (even in our study PSC, i.e. group A vs open sternum, i.e.…”
Section: Discussionmentioning
confidence: 53%
“…лих внутрішньоаортальна балонна контрапульсація неприйнятна для немовлят. Таким чином, відстрочене зведення грудини є однією з небагатьох методик, що дає змогу збільшити серцевий викид і є доступною для рутинного застосування в дітей перших місяців життя [4].…”
unclassified